Aortic sinus diameter in middle age is associated with body size in young adulthood. Issue 9 (1st November 2017) - Hernesniemi, Jussi A; Heiskanen, Jarkko; Ruohonen, Saku; Kartiosuo, Noora; Hutri-Kähönen, Nina; Kähönen, Mika; Jokinen, Eero; Tossavainen, Päivi; Kallio, Merja; Laitinen, Tomi; Lehtimäki, Terho; Viikari, Jorma S A; et al.
Abstract : Objective: Aortic sinus dilatation can lead to aortic valve regurgitation or even aortic dissection. Our objective was to examine the association between body surface area (BSA) measures from childhood to middle age and aortic sinus diameter in middle age. Understanding the relation of these two clarifies how aortic size is normally determined. Methods: Cardiovascular Risk in Young Finns Study is a longitudinal study with follow-up of over 31 years (1980–2011). The study comprises information of body composition from multiple time points of 1950 subjects with cardiac ultrasound measurements made in 2011. The association between BSA in different ages and aortic sinus diameter in middle age was analysed by linear regression modelling adjusted with age, sex and diastolic blood pressure. Missing BSA values were derived for each life year (ages 3–33 years) from subject-specific curves for body weight and height estimated from longitudinal measurements using mixed model regression splines. Results: BSA estimates in early 20s are most strongly associated with aortic sinus diameter in middle age. Top association was observed at age 23 years with one SD increase in estimated BSA corresponding to 1.04 mm (0.87–1.21 mm) increase in aortic diameter. Increase in body weight beyond early 20s does not associate with aortic sinus diameter, and the association between middle age BSA and aortic size is substantially weaker (0.74 mm increase (0.58–0.89 mm)). These results were confirmed in a subpopulation using only measured data. Conclusion: The association between aortic sinus diameter and BSA is stronger when considering BSA in young adulthood compared with BSA in middle age.